Subclinical Hypothyroidism in Pregnancy - A Case Series (Bangladesh Journal of Medical Science, 2017)
Background: Effects of overt hypothyroidism on pregnancy outcomes and foetal development are well established and treatment protocol is reputable.Method and material: The prevalence and effects of subclinical hypothyroidism (SCH) on pregnancy are not yet clear. Hence, universal screening of all pregnant women is still debatable and treatment of detected sub clinical hypothyroidism is yet to have general consensus as data regarding beneficial effects of treatment to mother and foetus in SCH cases is inadequate.Result: Odisha is a known endemic area of Iodine deficiency and reports of occurrences of SCH in Odisha are very limited. This study is a case series, done to detect the prevalence of SCH in pregnancy in the ante-natal unit of a medical college and hospital catering to a large population of Odisha.Conclusion: This prospective study included screening of the pregnant women for thyroid function and follow up of the cases with SCH till confinement to record any adverse effects of the thyroid dysfunction on obstetric outcome.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.53-60